Comparative Analysis of Tesla and Ford: Investment Recommendations Based on the 7Ps Marketing Portfolio and Porter’s Five Forces Model - Su, Tong (Transactions on Economics, Business and Management Research, 2024)
Investors increasingly focus on identifying favourable investment opportunities in the rapidly developing automotive industry. This study aims to analyse Tesla and Ford comprehensively, focusing on their financial performance, strategic positioning, and product strategies. This study evaluated the investment potential of these two significant companies using financial ratio analysis, Porter’s Five Forces Analysis, and the 7Ps framework. The analysis results show that although Tesla has demonstrated significant growth and innovation capabilities, its investments in autonomous driving, battery, and sustainable energy solutions have placed it in a favourable position in the future market. However, with its long history and extensive market coverage, Ford has demonstrated robustness and adaptability in the traditional automotive market. The research conclusion is an investment recommendation based on the comparative advantages and disadvantages of the two companies. Tesla’s advantage lies in its forward-looking technology and market leadership, while Ford’s lies in its stable financial performance and market adaptability. This analysis provides valuable insights for investors and lays the foundation for future investors’ choices and investments.